2023
DOI: 10.1017/sjp.2023.14
|View full text |Cite
|
Sign up to set email alerts
|

How do you Behave as a Psychometrician? Research Conduct in the Context of Psychometric Research

Abstract: The identification of fraudulent and questionable research conduct is not something new. However, in the last 12 years the aim has been to identify specific problems and concrete solutions applicable to each area of knowledge. For example, previous work has focused on questionable and responsible research conducts associated with clinical assessment, measurement practices in psychology and related sciences; or applicable to specific areas of study, such as suicidology. One area of study that merits further stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Firstly, the majority of manuscripts were published under restricted access, limiting the availability of research findings to a broader audience (Table 2). Concerningly, none of the included manuscripts utilized preregistration, an essential tool in countering questionable research practices and particularly relevant in psychometric research (Christensen et al, 2019;Gomes et al, 2022;Nosek et al, 2015;Tackett et al, 2019;Flores-Kanter & Mosquera, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, the majority of manuscripts were published under restricted access, limiting the availability of research findings to a broader audience (Table 2). Concerningly, none of the included manuscripts utilized preregistration, an essential tool in countering questionable research practices and particularly relevant in psychometric research (Christensen et al, 2019;Gomes et al, 2022;Nosek et al, 2015;Tackett et al, 2019;Flores-Kanter & Mosquera, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Within psychometric studies, recent research has identified questionable research conduct that can potentially threaten the validity and reliability of psychometric research results (Manapat et al, 2023). To ensure more rigorous and reliable psychometric research, good practices associated with transparency and open science have been recommended (Flake & Fried, 2020;Flores-Kanter & Mosquera, 2023). These include the adoption of open science practices such as preregistration, pre-printing, and the sharing of study materials, code, and data.…”
Section: Open Science In Psychometric Suicide Researchmentioning
confidence: 99%
See 3 more Smart Citations